The roles of the oncoprotein GOLPH3 in contractile ring assembly and membrane trafficking during cytokinesis. (26th January 2015) - Sechi, Stefano; Frappaolo, Anna; Belloni, Giorgio; Giansanti, Maria Grazia
Abstract : Cytokinesis is an intricate process that requires an intimate interplay between actomyosin ring constriction and plasma membrane remodelling at the cleavage furrow. However, the molecular mechanisms involved in coupling the cytoskeleton dynamics with vesicle trafficking during cytokinesis are poorly understood. The highly conserved Golgi phosphoprotein 3 (GOLPH3), functions as a phosphatidylinositol 4-phosphate (PI4P) effector at the Golgi. Recent studies have suggested that GOLPH3 is up-regulated in several cancers and is associated with poor prognosis and more aggressive tumours. In Drosophila melanogaster, GOLPH3 localizes at the cleavage furrow of dividing cells, is required for successful cytokinesis and acts as a key molecule in coupling phosphoinositide (PI) signalling with actomyosin ring dynamics. Because cytokinesis failures have been linked with pre-malignant disease and cancer, the novel connection between GOLPH3 and cytokinesis imposes new fields of investigation in cancer biology and therapy.